Junior High School Students’ Perception of the Using Fun Easy Learn Application in Vocabulary Learning - Riza Nur Muslimatun Nisa'Sirait; Ernita Daulay (IJECA (International Journal of Education and Curriculum Application), 2024)
Vocabulary is the most basic element that must be possessed in mastering and developing the four language skills. However, vocabulary acquisition is difficult for many EFL students in Indonesia. Faced with this situation, the role of English teachers is needed to find and implement new and different learning methods or strategies, so that vocabulary learning in the classroom becomes interesting learning for students. The purpose of this study is to explain the perceptions of EFL English students towards the use of a mobile application called Fun Easy Learn application and to find out the students' perceptions about the level of effectiveness of this application in learning English vocabulary in the classroom. The method used in this research is qualitative method. Data collection was done by using questionnaires through Google form then supported by interviews on the topic of students' perceptions of the usefulness and effectiveness of Fun Easy Learn application. Data analysis was done by frequency calculation and content analysis. This study was conducted in a private junior high school, SMP Al-Hidayah Medan, Indonesia. The participants in this study were 28 ninth grade students (17 boys and 11 girls). The results of data analysis were conducted through frequency calculation and content analysis which resulted in that most of the students' perceptions were happy and satisfied with the use of Fun Easy Learn app in vocabulary learning. Because by using Fun Easy Learn app they find: (1) Motivation; (2) Learning is not boring and stressful; (3) Helps understand and improve vocabulary; (4) Learning can extend the duration of learning time; and (5) Easy to navigate the Fun Easy Learn application. They also expressed the perception that Fun Easy Learn app is effective in learning English vocabulary, the emergence of this perception is because students find the benefits of this app namely (1) Improve memory; (2) Mastery of English vocabulary; and (3) Have an interest in learning English vocabulary. Students who participated generally expressed positive perceptions of the Fun Easy Learn application. Based on the results of this study, the researcher can recommend Fun Easy Learn application as a mobile application that can be used by English teachers as a learning media in English classes.